Endophytic bacteria induce thiamine (vitamin B1) production in oil palm (Elaeis guineensis) - Balia Yusof, Zetty Norhana; Johari, Nur Asna Faiqah; Zainal Abidin, Aisamuddin Ardi; Ismail, Nur Farhah Nabihan (Penerbit Universiti Sains Malaysia, 2024)
Thiamine or vitamin B1 is a micronutrient that has a crucial function in all living organisms and involved in several biochemical reactions. Concerning the capability of thiamine in inducing plant health, a study was carried out by applying bacterial endophytes (Pseudomonas aeruginosa and Burkholderia cepacia cultures) in four-month-old oil palm seedlings (Elaeis guineensis) via soil drenching technique to evaluate the effect towards thiamine. Spear leaves were sampled at day 0 to 14 to analyse the expression of gene coding for the first two enzymes thiamine biosynthesis pathway, THI4 and THIC via qPCR analysis. The gene expression by qPCR showed a significant increase of up to 3-fold while high-performance liquid chromatography (HPLC) analysis for quantification of thiamine and its derivatives accumulated ~ 20-fold in total thiamine when compared to control seedlings. However, concentration of thiamine metabolites was negatively correlated with the expression of THIC and THI4 gene transcripts suggesting post-transcriptional regulation mediated by an RNA regulatory element, a thiamine pyrophosphate (TPP) riboswitch. Our findings demonstrated that the application of bacterial endophytes affected thiamine biosynthesis and enhanced overall thiamine content. This might increase the plant’s resistance towards stress and would be useful in oil palm maintenance for maximum yield production.